Clobetasol propionate cream 0.025%: a topical therapeutic for dermatological disorders - R., Gnansekaran; Mohammad, Chand; Saini, Nirmal Kumar; Aggarwal, Vivek; Mishra, Sameer; Mehta, Surjit Singh; Satvantsinh, Bhabhor Rahul; Prasanna, Mure Sri Hari; Srikanth, Satu; Gupta, Alka (International Journal of Research in Medical Sciences, 2022)
Due to the anti-inflammatory and vasodilator effects of topical corticosteroids, they help in treating atopic eczema, psoriasis, chronic hand eczema, and localized vitiligo, among other dermatological diseases. Clobetasol propionate (CP) is the most popular topical medication used to treat plaque psoriasis. It has anti-inflammatory, antimitotic, antipruritic, and immunosuppressive characteristics. The USFDA has approved CP 0.025% cream for the treatment of moderate-to-severe psoriasis in adults. Propylene glycol, short-chain alcohols, and sorbitol-based emulsifiers are all recognized contact allergens, and the formulation has exhibited hypoallergenic effects. CP 0.025% is an effective and safe agent due to its high active ingredient penetration and minimal systemic absorption. The clinical experience of employing CP 0.025% cream in diverse dermatologic disorders is discussed in this case series, with a focus on its efficacy and safety.